Sarcomatoid squamous cell carcinoma - Singh, R.S. (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2008)
Sarcomatoid, or spindle cell squamous cell carcinoma (SCSC), is relatively uncommon, but may be encountered. It poses a challenge in differential diagnosis that includes other spindle cell neoplasms. We present a case where the lesion existed for 20 years and raised the potential of chronicity as a factor in inducing spindle cell morphology. Detailed immunohistochemical features are demonstrated, and discussion of the differential diagnosis is offered. The patient was an 89-year-old African-American female with an exophytic and polypoid mass of the right upper arm measuring 5.5 * 5.5 * 3.0 cm. The mass had been present for the last 20 years, and was gradually and very slowly increasing in size. After refusing surgery several times, she finally agreed to have an excision. The tumor proved to be SCSC.
Keywords: karcinom; kožni rak; rak (medicina)